The Multidimensional Effect of Financial Development on Total Factor Productivity: Evidence from Cross-country Panel Data - Çağatay Vişne; Ramazan Ekinci (Ekonomi, Politika & Finans Araştırmaları Dergisi, 2025)
In this paper, we estimate the impact of financial development on total factor productivity (TFP) using panel data for the years 2002 to 2019. Using the Driscoll-Kraay Standard Error (DKSE) approach, we analyse how financial development and its sub-indices (financial institutions and financial markets) are related to TFP. The results confirm the existence of a positive and significant relationship between financial development and TFP, suggesting that financial development plays a facilitating role in TFP. For the robustness analysis, it is concluded that financial institutions, one of the subcomponents of financial development, have a positive and significant effect on TFP, while financial markets do not have a significant effect on TFP. Moreover, while the effect of financial development on TFP is positive and significant in developing countries, there is no clear evidence of such an effect in developed countries. Among the control variables included in the model, trade openness, foreign direct investment, and economic growth have a positive effect on TFP, while human capital has a negative effect. Only innovation is not statistically significant. Furthermore, it is confirmed that institutional quality indicators also have a positive impact on total factor productivity when included in the model. Our results suggest that policies favouring financial development should be pursued further in order to correct the mismatch in resource allocation and thus promote TFP growth.